“The exaltation of the figure of the lawyer”: the mobilization of the OAB/RS during the arrest of communists in 1975 (Tempo e Argumento, 2022)
This paper analyze the performance of the Rio Grande do Sul chapter of the Brazilian Bar Association (OAB/RS) during the arrest of activists of the Brazilian Communist Party (PCB) in march 1975. This case was the result of a process that took place throughout the dictatorship in which the entity was placed as a voice of opposition to the violence committed by the civil-military dictatorship. Within this, it was decisive the performance of communist lawyers within professional organizations, often in a prominent position. The arrests were made as a result of investigations related to Rio de Janeiro and São Paulo, and would have to do with the actions of militants of the party in the MDB. This event was decisive for the position taken by the entity during the political opening. Likewise, by adopting an active public attitude in denouncing the prisons, the entity contributed to the process of strengthening the fight for human rights and democracy.Keywords: OAB (Brazilian Bar Association); lawyers; PCB; civil-militar dictatorship.